Mengukuhkan Otensitas Tradisi Hukum Campursari Dalam Sistem Hukum Nasional - Shinta Dewi Rismawati (Jurnal Hukum Islam, 2017)
The tradition of the legal system is actually a human product based on the three ordinates. There are human, environment and law, and then the legal traditions that exist in the world become diverse. The development of Indonesian law traditions is a timeless and dynamic project. Therefore, although the dominance of civil law is thick in the tradition of Indonesian, but the creativity, innovation and synthesis method can make the tradition of Indonesian legal system is tradition of campursari (mixed). As a result, the Civil law tradition, the common law tradition and the Islamic law tradition are easily found in the practice of law in Indonesia. The tradition of constructing a campursari-style legal system needs to be established and developed to create an Indonesian law system based on Pancasila, but does not ignore the present aspect.